Impact of Circadian Rhythms on the Development and Clinical Management of Genitourinary Cancers - Kaur, Priya; Mohamed, Nihal E.; Archer, Maddison; Figueiro, Mariana G.; Kyprianou, Natasha (Frontiers in Oncology, 2022)
The circadian system is an innate clock mechanism that governs biological processes on a near 24-hour cycle. Circadian rhythm disruption (i.e., misalignment of circadian rhythms), which results from the lack of synchrony between the master circadian clock located in the suprachiasmatic nuclei (SCN) and the environment (i.e., exposure to day light) or the master clock and the peripheral clocks, has been associated with increased risk of and unfavorable cancer outcomes. Growing evidence supports the link between circadian disruption and increased prevalence and mortality of genitourinary cancers (GU) including prostate, bladder, and renal cancer. The circadian system also plays an essential role on the timely implementation of chronopharmacological treatments, such as melatonin and chronotherapy, to reduce tumor progression, improve therapeutic response and reduce negative therapy side effects. The potential benefits of the manipulating circadian rhythms in the clinical setting of GU cancer detection and treatment remain to be exploited. In this review, we discuss the current evidence on the influence of circadian rhythms on (disease) cancer development and hope to elucidate the unmet clinical need of defining the extensive involvement of the circadian system in predicting risk for GU cancer development and alleviating the burden of implementing anti-cancer therapies.